Maternal Plasma Lipid Concentration in Early Pregnancy and Risk of Preeclampsia - Chughtai, Faiqa; Syed, Humna; Shams, Mehwish Ara; Akhter, Amim Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the relationship between maternal plasma lipid concentration in early pregnancy and risk of preeclampsia.Study Design: Cross-sectional study.Place and Duration of Study: Gynecology and Obstetrics Department Pak Emirates Military Hospital, Rawalpindi Pakistan, Jan 2019 to Jan 2020.Methodology: A total of 500 pregnant women who came for routine antenatal checkup and underwent serum lipid profile testing at 13th week of pregnancy were included in our study. They were followed up till the end of pregnancy for any signs and symptoms of pre-eclampsia. Age and lipid profile parameters were correlated with the presence of preeclampsia in the study participants.Results: Out of 500 pregnant women studied, 443(88.6%) had no preeclampsia during the course of pregnancy while 53(11.4%) had preeclampsia. Mean age of participants was 33.72±6.731 years. With binary logistic regression analysis, it was found that raised levels of total cholesterol, triglycerides and low density lipoprotein cholesterol at 13 weeks of pregnancy had statistically significant relationship with presence of preeclampsia later among the target population.Conclusion: Deranged lipid profile emerged as strong predictor of preeclampsia in our target population. Raised total cholesterol level, triglyceride levels and low density lipoprotein levels were significantly more in patients who developed preeclampsia as compared to those who did not develop this condition.